Engineering Agile Big-Data Systems. - Feeney, Kevin. (River Publishers, 2018)
Engineering Agile Big-Data Systems outlines an approach to dealing with these problems in software and data engineering, describing a methodology for aligning these processes throughout product lifecycles.